Research methods for social work - Rubin, Allen (Pacific Grove Brooks/Cole Pub. Co., 1997)
In this revised edition of the text, the authors retain the comprehensive approach, while including a more balanced content about quantitative and qualitative methods. The text includes a greater emphasis on alternative thinking and the debate about quantitative and qualitative research.
Keywords: Social service -- Research -- Methodology. Social Work. Research